Multimodal therapeutic options for esophageal perforations—a single-center experience - Gruber, Maximilian; Kollmann, Lars; Friso Lock, Johan; Flemming, Sven; Reimer, Stanislaus; Brand, Markus; Wiegering, Armin; Meining, Alexander; Aleksic, Ivan; Germer, Christoph-Thomas; Seyfried, Florian (Frontiers in Surgery, 2025)
BackgroundEsophageal perforation is a life-threatening condition with a high mortality rate. The current therapeutic options range from conservative to endoscopic to surgical treatment. We aimed to compare specific patterns of multimodal management of spontaneous vs. other esophageal perforations.MethodsThe data from all consecutive patients diagnosed with either spontaneous (Boerhaave syndrome, BS) vs. other esophageal perforation (OEP) between 2010 and 2023 were prospectively collected and retrospectively analyzed. The primary endpoint was in-hospital mortality. The secondary endpoints were overall complications (Comprehensive Complication Index, CCI), therapy-associated complications, oral nutrition at discharge, and length-of-stay.ResultsIn total, 32 patients were identified, of whom 15 were diagnosed with BS and 17 with OEP. Initially, 11/32 (34.4%) were primarily treated endoscopically, 12/32 (37.8%) with surgery, and 8/32 (25.0%) with a combined treatment. Patients with BS had larger perforations (22.50 vs. 15.00 mm, p = .05) and higher complication scores (CCI: 61.80 vs. 45.60, p = .076). Over the course, the primary therapeutic regimen (endoscopic or local surgical treatment) had to be escalated in 36.4% of the patients. Overall, the in-hospital mortality rate was 9.4% (3/32 patients), with a strong trend toward a higher mortality rate in patients with BS (20.0 vs. 0.0%, p = .053). Diagnoses of BS and sepsis at admission (β = 28.387, p = .012) were independent risk factors for a higher CCI score.ConclusionsBS and sepsis at admission are risk factors for a complicated course. Endoscopy is the first choice for diagnosis and initial treatment. Patients with mediastinal gross contamination or large defects usually need surgical intervention, which should not be delayed.